40Ar/39Ar and (U-Th)/He model age signatures of elusive Mercurian and Venusian meteorites - Jourdan, Fred; Eroglu, E. (John Wiley & Sons, Inc., 2017)
No meteorites from Mercury and Venus have been conclusively identified so far. In this study, we develop an original approach based on extensive Monte Carlo simulations and diffusion models to explore the radiogenic argon (40Ar*) and helium (4He*) loss behavior and the range of 40Ar/39Ar and (U-Th)/He age signatures expected for a range of crystals if meteorites from these planets were ever to be found. We show that we can accurately date the crystallization age of a meteorite from both Mercury and Venus using the 40Ar/39Ar technique on clinopyroxene (± orthopyroxene) and that its 40Ar/39Ar age should match the Pb-Pb age. At the surface of Mercury, phases like albite and anorthite will exhibit a complete range of 40Ar* loss ranging from 0% to 100%, whereas merrillite and apatite will show 100% 4He* loss. By measuring the crystal size and diffusion parameters of a series of plagioclase crystals, one can inverse the 40Ar* loss value to estimate the maximum temperature experienced by a rock, and narrow down the possible pre-ejection location of the meteorite at the surface of Mercury. At the surface of Venus, plagioclase and phosphate phases will only record the age of ejection. The (U-Th)/He systematics of merrillite and apatite will be, respectively, moderately and strongly affected by 4He* loss during the transit of the meteorite from its host planet to Earth. Finally, meteorites from Mercury or Venus will each have their own 40Ar/39Ar and (U-Th)/He isotopic age and 38Arc cosmic ray exposure age signatures over a series of different crystal types, allowing to unambiguously recognize a meteorite for any of these two planets using radiogenic and cosmogenic noble gases. © 2017 The Meteoritical Society.